Concise Oxford English dictionary - Soanes, Catherine; Stevenson, Angus (Oxford University Press, 2008)
"The Concise Oxford English Dictionary presents a picture of English today. It includes: rich, authoritative coverage of the English language including scientific and technical terms as well as English from around the world; accurate description for each word, with real examples and usage notes drawn from the evidence of the Oxford English Corpus; clear layout to help you find the information you need; and a new centre section that explores the richness of the English language past and present. This dictionary contains over 240,000 words, phrases, and meanings."--BOOK JACKET.